PERAN KEPOLISIAN DAERAH JAWA TENGAH DALAM PENANGGULANGAN ISIS DI JAWA TENGAH - Satya Marpaung, Irfan (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
Terrorism started at fundamental thoughts towards meaning and interpretation of religion concept or law that defined by religion in this case Islam. Related to terrorism, one of terrorism organization in the earlier of this yearÂ that threatening public discipline is ISIS. ISIS isÂ international terrorism organization which has track record so harmful if this organization freely doing activity in region or country. The ISIS influences considered has been access in Indonesia especially Central Java so those things rely on the role of Polda Jateng as police institutions that has responsibility against public discipline and security. And it will appear some question in this research that is how the role of Polda Jateng in prevention ISIS influences. In this research used qualitative research method by doing interview to some informant. Sampling techniques that used to choose informant is purposive sample, with purposive techniques so informant had been choosed by researchers is Kasat Brimob Polda Jateng, Kasubdit IV Intelkam Polda Jateng, Kasubdit Bintibluh Ditbinmas Polda Jateng, Kapolres Sukoharjo and Polda Jateng corps. Then the result of interview analyzed to know the role decription of Polda Jateng in prevention ISIS influences. Keywords : role, terrorism, prevention ISIS influences, Polda Jateng.